THE EXPRESSIONS OF DIRECTIVE SPEECH ACTS IN THE FILM ENTITLED â€œMARY QUEEN OF SCOTSâ€ FILM (A PRAGMATICS APPROACH) - Nataliya, Nataliya; Marmanto, Sri (Kajian Linguistik dan Sastra, 2020)
This research was conducted to find out the types of directive speech acts in the film entitled Mary Queen of Scots, the way the speakers expressed those types, and the reasons underlying the speakers to utter those types. This research uses Pragmatics approach. This study was designed with descriptive research. The analyzed data were all the dialogs which expressed the types of directive speech acts of Mary Queen of Scots film. The total sampling technique is used in taking the data analysis. The researcher analyzed the data found in the film based on problem statements. First, the findings are as follows 6 types of directive speech acts consisting of Command, 13 data (42%), Request 3 data (16%), Question 9 data (30%), Suggestion 2 data (6%), Prohibition 1 datum (3%), and Warning 1 datum (3%). Second, three ways of expressing politeness strategies are used by the characters in Mary Queen of Scots. They were Bald On-Record, Positive Politeness, and Off-Record. At last, the reasons characters expressed the directive speech act were to show hearerâ€™s duty, to show anger expression, to respect the hearer, to seek agreement, and find the reason for uttering certain expression.Â Keywords: pragmatics, directive, speech acts, politeness strategies, film.